A young man presenting with encephalopathy and seizures secondary to SARS-CoV-2. Issue 3 (24th March 2021) - Jalil, Bilal Athar; Ijaz, Mohsin; Khan, Amir Maqbul; Ledbetter, Thomas Glenn
Abstract : COVID-19 has now emerged from a respiratory illness to a systemic viral illness with multisystem involvement. There is still a lot to learn about this illness as new disease associations with COVID-19 emerge consistently. We present a unique case of a neurological manifestation of a patient with structural brain disease who was COVID-19 positive and developed mental status changes, new-onset seizures and findings suggestive of viral meningitis on lumbar puncture. We also review the literature and discuss our case in the context of the other cases reported. We highlight the value of considering seizures and encephalopathy as one of the presenting features of COVID-19 disease.